Questionnaire on body awareness of postural habits in young people: construction and validation - Debora Soccal Schwertner; Raul Alexandre Nunes da Silva Oliveira; Thais Silva Beltrame; Renata Capistrano; Juliano Maestri Alexandre (Editora Champagnat, 2018)
Abstract Introduction: The postural deviations associated with the changes in the habits of young people have increased over the last decades. Investigating the subject by way of a self-perception questionnaire allows one to understand the level of awareness the individual has concerning his/her postural habits. Objective: Designing a self-perception evaluation questionnaire about the postural habits of young people and to validate, pre-test, verify the reliability and the internal consistency of this instrument. Methods: The validity of the content was determined by 10 judges. The study involved young people (15 - 18 years old) from Florianopolis/Brazil. The questionnaire was pre-tested, applied to 15 youthful who provided qualitative information about it. The reproducibility was analyzed by way of a test-retest with 40 students, in a one-week gap, and was analyzed by interclass correlation coefficient. The internal consistency was analyzed by Cronbach's alpha with 679 students. A 5% significance level was adopted. Results: Concerning to the validation of content, the questionnaire presented a total coefficient of 0.28 and 72% concordance was observed amongst the reviewers. The interclass correlation coefficient (test-retest) indicated acceptable reproducibility values (R = 0.66, 0.74 and 0.59; p < 0.001), with a decrease in the object-carrying dimension (R = 0.32; p = 0.04). The questionnaire was considered suitable, quick and easy to fill in. The internal consistency presented a value of 0.80. Conclusion: The questionnaire on body awareness of postural habits in young people is a valid instrument with good repeatability and reliability, its use can be recommended with teenagers showing the same profile as those used in this study.